2013
DOI: 10.1002/hbm.22248
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in Alzheimer's disease are related to functional connectivity alterations in the salience network

Abstract: Neuropsychiatric syndromes are highly prevalent in Alzheimer's disease (AD), but their neurobiology is not completely understood. New methods in functional magnetic resonance imaging, such as intrinsic functional connectivity or "resting-state" analysis, may help to clarify this issue. Using such approaches, alterations in the default-mode and salience networks (SNs) have been described in Alzheimer's, although their relationship with specific symptoms remains unclear. We therefore carried out resting-state fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
134
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 55 publications
12
134
0
1
Order By: Relevance
“…The SN, with the anterior insula as its integral outflow hub, assists target brain regions to generate behavioral responses to salient stimuli 10 . In a previous study of our group, we showed that connectivity in the right insula of AD patients was related to symptoms of agitation, disinhibition, irritability, euphoria, and aberrant motor behavior 4 . Moreover, task-based functional MRI studies showed that hyperactivity of anterior insula has been consistently implicated with anxiety disorders 11 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The SN, with the anterior insula as its integral outflow hub, assists target brain regions to generate behavioral responses to salient stimuli 10 . In a previous study of our group, we showed that connectivity in the right insula of AD patients was related to symptoms of agitation, disinhibition, irritability, euphoria, and aberrant motor behavior 4 . Moreover, task-based functional MRI studies showed that hyperactivity of anterior insula has been consistently implicated with anxiety disorders 11 .…”
Section: Discussionmentioning
confidence: 67%
“…Although these networks showed alterations, some anatomical structures did not exhibit cortical atrophy, which suggests that behavioral disorders may be triggered by disruptions in functional connectivity with or without the atrophy of the structures of these networks. In addition, NPS could be related to disruptions in functional connectivity before evidence for cortical changes 4 . Voxel-based Morphometry (VBM) has recently been used in research to verify the possible correlation between GM density and NPS.…”
mentioning
confidence: 99%
“…Accordingly, both inferior frontal gyrus (both sides, r3n12 and r7n12) and the frontal portion of the DMN (r1n4) proved to be positively correlated, also in contrast to controls. The relationship between DMN, salience and ECNs is under investigation, but recent studies defined that DMN and salience work oppositely, meaning that the increase of the first is followed by a decrease in the second, and vice‐versa [Balthazar, et al, 2014]. Some authors suggest that this mechanism involves a mediation of activity executed by the salience network guiding the focus on internal (DMN) or external (ECN) process and stimulus [Liang et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Heightened salience network connectivity in healthy individuals has been associated with negative emotional reactivity and glucocorticoid levels (e.g., cortisol), a neuroendocrine index of the stress response (30). In AD, increased salience network connectivity relates to neuropsychiatric hyperactivity symptoms (e.g., agitation, irritability, aberrant motor behavior, disinhibition, and euphoria) (31). Neurodegeneration of medial temporal structures that support emotion inhibition (27,28) and lateral temporal structures that promote socioemotional processes, including evaluation of faces (32), prosody (33), intention (34), and trustworthiness (35), may alter affective physiology, behavior, and experience in MCI and AD.…”
mentioning
confidence: 99%